(untitled) (Research, Society and Development, 2022)
This study aimed to assess the economic viability of managing the Strypodendron adstringens Mart. Coville in the Cerrado sensu stricto in North of Minas Gerais. To achieve this goal we analyzed the economic feasibility of four management plans under selective cuts with 40, 50, 60 and 70% of basal area removed (G). The method consisted of building a cash flow for the species with a planning horizon for ten years. After obtaining the cash flow, with the help of economic engineering resources, we evaluated the financial indicators. These indicators consisted of Net Present Value (NPV), Internal Rate of Return (IRR), Discounted Payback period (PP) and Break-even Point (BEP). The results presented economically viable for all plans analyzed. But the plan 70% of basal area removed, stood out from the rest. Therefore it is concluded that the production of barks of barbatimão is economically viable since the intervention takes place in the percentage of 70% basal area within a sustainable management system.